2002
DOI: 10.1021/ja012659q
|View full text |Cite
|
Sign up to set email alerts
|

The Active Site of Cellobiohydrolase Cel6A fromTrichoderma reesei:  The Roles of Aspartic Acids D221 and D175

Abstract: Trichoderma reesei cellobiohydrolase Cel6A is an inverting glycosidase. Structural studies have established that the tunnel-shaped active site of Cel6A contains two aspartic acids, D221 and D175, that are close to the glycosidic oxygen of the scissile bond and at hydrogen-bonding distance from each other. Here, site-directed mutagenesis, X-ray crystallography, and enzyme kinetic studies have been used to confirm the role of residue D221 as the catalytic acid. D175 is shown to affect protonation of D221 and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
155
2
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(172 citation statements)
references
References 58 publications
(128 reference statements)
14
155
2
1
Order By: Relevance
“…The lack of a candidate Asp or Glu catalytic base is evident in some inverting glycoside hydrolases. In GH6 enzymes, the identity of the Brønsted base has remained particularly elusive, and a "Grotthus"-style mechanism, in which a remote amino acid activates an active site water via a string of solvent molecules, remains the likely mechanism (21). It is likely, therefore, that CtCel124 also hydrolyzes glycosidic bonds through a Grotthus-style mechanism, although small nucleophilic ions such as thiols, acetate, or phosphate ions may fulfill the role of the catalytic base by activating the nucleophilic water.…”
Section: Ctcel124-cbm3amentioning
confidence: 99%
“…The lack of a candidate Asp or Glu catalytic base is evident in some inverting glycoside hydrolases. In GH6 enzymes, the identity of the Brønsted base has remained particularly elusive, and a "Grotthus"-style mechanism, in which a remote amino acid activates an active site water via a string of solvent molecules, remains the likely mechanism (21). It is likely, therefore, that CtCel124 also hydrolyzes glycosidic bonds through a Grotthus-style mechanism, although small nucleophilic ions such as thiols, acetate, or phosphate ions may fulfill the role of the catalytic base by activating the nucleophilic water.…”
Section: Ctcel124-cbm3amentioning
confidence: 99%
“…The GH6 catalytic acid has been identified as a conserved aspartic acid (Asp-221 in H. jecorina Cel6A (HjeCel6A) and Asp-274 in TfuCel6B) (29,30). Several potential titratable residues nearby have been proposed to be the catalytic base (29 -32), but none of these residues have been found in crystal structures within the necessary distance to act directly as the base.…”
mentioning
confidence: 99%
“…Instead, the predominant mechanism for GH6 hydrolysis proposed to date from several structural studies involves a water wire or Grotthuss mechanism. Several structures reveal a nucleophilic water molecule near the anomeric carbon stabilized by a serine residue on the "active center" loop (residues 175-183 in HjeCel6A and 226 -234 in TfuCel6B) (23,30). This water molecule is hydrogen-bonded to a second water molecule, which in turn hydrogen-bonds to a conserved aspartate (Asp-175 in HjeCel6A and Asp-226 in TfuCel6B).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Structural studies have revealed that cellobiohydrolases of this family have tunnel-like catalytic sites covered by flexible loops, which are not necessarily conserved in endoglucanases (Rouvinen et al, 1990;Spezio et al, 1993). This family is also known for its unusual 'Grotthus-type' inverting mechanism: the enzymes appear to lack a general base residue that would activate a catalytic water molecule for direct nucleophilic attack; instead, observations of ordered water molecules near the active site led to the proposal that an additional water molecule is involved in hydrolysis, serving to bridge between the catalytic water molecule and the proton-accepting residue (Koivula et al, 2002).…”
Section: Introductionmentioning
confidence: 99%